DEVELOPMENT OF A LITERATURE CURRICULUM FOR ENHANCING EMPATHY OF LOWER SECONDARY STUDENTS - Pumpachart, Thanachaporn; Jamjuree , Danulada; Dudsdeemaytha, Jitra; Sounsamut, Pram (Journal of Buddhist Anthropology, 2021)
The Objectives of this research article were to 1) develop empathy characteristics among lower secondary school students; 2) to develop a literature curriculum to enhance empathy characteristics among lower secondary school students; and 3) to study the effectiveness of the literature curriculum to enhance the empathy characteristics. The research design was research and development (R&D), which was divided into the following three phases: Phase I: the researcher synthesized theoretical frameworks and interviewed the experts in the fields. The results showed that there were three characteristics of empathy characteristics among lower secondary school students, which included: 1) understanding the feelings and behavior of others; 2) consideration; and 3) appropriate responses. Phase II: the researcher developed the curriculum from Social Constructivism by adapting the Literature Circle approach, Transformative Learning, and Empirical Learning for Literacy and then conducting the pilot study. The results demonstrated that the curriculum was comprised of four units, based on genre, such as movies, short stories, novels, and poetry. There were four learning procedures in each unit. They were 1) specifying learning objectives according to the interests of students; 2) studying literature through the use of the Literature Circle; 3) applying and connecting to lessons learned for new situations; and 4) reflective practice and learning evaluation. Phase III: the researcher utilized the curriculum with the sample group of 26 students in order to evaluate the effectiveness of the curriculum by using Repeated - measure ANOVA. It was found that the development of enhanced empathy increased during the course significantly at .05. The were different average values from using Repeated-measure at least twice. (F = 132. 132, df = 2.245, 56.134, p = .00)